2021
DOI: 10.1371/journal.pone.0252075
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and coping strategies in relation to mental health outcomes in people with cancer

Abstract: Considering the importance of psychological variables on health-related processes, this study investigated the role of resilience and coping strategies in relation to health. The aim of this research was to explore the underlying association between these aspects for the better understanding of the effect of psychosocial variables on mental health in cancer. This information could lead to the design of adapted psychological interventions in cancer. Participants with different diagnosis of cancer were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The findings of this current study are novel as previous studies, to the best of our knowledge have not explored the relationship between resilience and coping particularly among patients with hypertension. However, it is not surprising as other studies have found that the positive contribution of higher levels of resilience and an adaptive coping strategy improves the level of health of patients with chronic diseases (Cal et al, 2015;Ghanei Gheshlagh et al, 2016;Li and Miller, 2017;Popa-Velea et al, 2017;Macía et al, 2021;Zapater-Fajarí et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…The findings of this current study are novel as previous studies, to the best of our knowledge have not explored the relationship between resilience and coping particularly among patients with hypertension. However, it is not surprising as other studies have found that the positive contribution of higher levels of resilience and an adaptive coping strategy improves the level of health of patients with chronic diseases (Cal et al, 2015;Ghanei Gheshlagh et al, 2016;Li and Miller, 2017;Popa-Velea et al, 2017;Macía et al, 2021;Zapater-Fajarí et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…While research has found an association between coping through emotional support seeking and higher quality of life and general mood, [52] interestingly, while emotional support was a signi cant negative predictor for depression and anxiety, it was not signi cant for suicidal ideation. Suicidal ideation, therefore, poses a special speci c problem where an individual might be more sensitive to the potential rejection while seeking emotional support as is explained by the Interpersonal-Psychological Theory of suicide.…”
Section: Associations Of Mental Health Facetsmentioning
confidence: 86%
“…The American Psychological Society defines resilience as a process of “bouncing back” from difficult experiences and “adapting well in the face of adversity, trauma, tragedy, threats or significant sources of stress” ( 25 ). It has been found that strengthening individual resilience may help the adoption of positive coping styles, and promote mental health and psychological wellbeing ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%